Measuring range the application of Organizational Identification philosophy in the Zain Company for Communications - Alaulddin B. Jawad , Dr. Salah Al-Deen Al-Kubaisy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study attempts to test the possibility of developing organizational performance in Zain Telecom by adapting the philosophy and concept of Organizational Identification and its dimensions, the most important of which are (Organizational Identification, organizational loyalty, organizational affiliation).To achieve the goal, the research relied on the questionnaire method, which is one of the methods of collecting information in field studies.